Assess the Knowledge Regarding Human Breast Milk Banking Among Women in Selected Rural Area of District Mohali Punjab, With A View to Develop Information Booklet (International Journal of Nursing Education, 2022)
Background: Mother’s milk is the best food for growth and development of an infant. Every mother shouldbreastfeed her infant. However, if, under certain circumstances, she is unable to feed her infant directly, herbreast milk should be expressed and fed to the infant, particularly in preterm and other high-risk infants. Aim:To assess the knowledge regarding human breast milk banking among women in selected rural area of districtMohali Punjab, with a view to develop information booklet. Material and Methods: A quantitative study“descriptive design.” Used in present study. Results: The sample of 60 married women were selected by usingnon probability purposive sampling technique. Self -structured knowledge questionnaire was used to assess theknowledge regarding infant rearing practices. The study revealed that maximum women (22%) had excellentlevel of knowledge followed by (18%) had good level of knowledge, (45%) had average level of knowledge and(15%) had poor level of knowledge.
Keywords: knowledge, Breast Feeding, Breast Milk Banking, Women